The great masquerader of pancreatic tuberculosis - Kheng, Hooi Chan; Harivinthan Sellappan; Thanesh Kumar Maiyauen; Azlanudin Azman; Mohd Firdaus Mohd Hayati (Springer Nature, 2022)
Background: Pancreatic tuberculosis is a rare clinical entity. It represents a diagnostic challenge as the clinical presentation may mimic pancreatic malignancy. Case presentation: A 66-year-old gentleman presented with an incidental finding of a pancreatic tail mass on routine ultrasonography of the abdomen whilst working up on chronic kidney disease. He denied abdominal pain, fever, night sweats, constitutional symptoms or tuberculosis contact. On examination, there was no palpable mass per abdomen. The tumour marker of Ca 19-9 was normal. Ultrasonography revealed a lobulated heterogeneous hypovascular and hypoechoic mass at the tail of the pancreas. Contrast-enhanced computed tomography (CT) of the thorax and abdomen revealed a thickened right pleura, right pleural effusion with right lung collapsed consolidation and multiple mediastinal lymph nodes. There is an ill-defined hypodense mass seen in the tail and body of the pancreas measuring 3 × 7 × 3 cm with the presences of calcification within. The constellation of CT findings suggests a pancreatic malignancy with metastasis to the lungs. Endoscopic ultrasonography (EUS) assessment showed an irregular hypoechoic mass measuring 3.0 × 2.7 cm at the tail of the pancreas. Multiple rounded hypoechoic lesions were also seen scattered within the body of the pancreas with multiple enlarged para-aortic lymph nodes. A fine-needle aspiration biopsy of the lesion was consistent with granulomatous inflammation. The diagnosis of disseminated tuberculosis was made. The patient was subsequently started on antitubercular medication and recovered well. Conclusion: A high index of suspicion is needed to diagnose pancreatic tuberculosis, especially in patients whose radiological imaging shows a pancreatic mass with necrotic peripancreatic lymphadenopathy in endemic countries. EUS-guided fine-needle aspiration is the diagnostic modality of choice, and vigorous attempts should be made at obtaining a preoperative histological or bacteriological diagnosis to avoid unnecessary surgery.